Серум сCD40L и галектин-3 у прогнозији пацијената са акутним исхемијским можданим ударом: Серум сCD40L и галектин-3 код акутног исхемијског можданог удара - Chen, Zhiqin; Xiao, Quanhua; Luo, Kunqing; Lin, Shuping; Fan, Zhaoyang; Lai, Xianliang (Journal of Medical Biochemistry, 2025)
[Objective] To explore the value of serum soluble CD40 ligand (sCD40L) and galectin-3 (galectin-3) for predicting the therapeutic effect and prognosis of patients with acute ischemic stroke (AIS). [Methods] 180 AIS patients who were admitted to the hospital between March 2023 and March 2025 were chosen to serve as research participants. All patients received emergency treatment with tenalplase (TNK-tPA) combined with Xuesaitong. Based on the therapeutic impact, patients were split into two groups: an effective group and an ineffective group. The levels of serum sCD40L and galectin-3 in the two groups before treatment and 4 weeks after treatment were detected and compared. Following discharge, all patients were monitored for three months, and based on their modified RANKIN scale (mRS) score, those with a good prognosis and those with a bad outlook were divided into two groups. Utilizing multivariate logistic regression analysis, the risk factors impacting poor prognosis and inadequate treatment in AIS patients were examined. Serum levels of sCD40L and Galectin-3 were analyzed using a receiver operating characteristic (ROC) curve to determine their prognostic value for poor prognosis and ineffective treatment in AIS patients. [Results] Among the 180 research subjects, 146 were effectively treated (effective group), and 34 were ineffective (ineffective group). There were 142 patients with a good prognosis and 38 patients with a poor prognosis, with an incidence of poor prognosis of 21.11%. After four weeks of treatment, serum levels of sCD40L and Galectin-3 were lower in the successful group than in the unsuccessful group (P<0.05). Serum levels of sCD40L and galectin-3 were both greater in the group with a poor prognosis than in the group with a favorable one (P<0.05). Multivariate logistic regression analysis revealed that AIS patients with high serum levels of galectin-3 and sCD40L were at risk for both insufficient treatment and a poor outcome (P<0.05). The areas under the curve (AUCs) of serum Calectin-3 and sCD40L for predicting treatment ineffectiveness in AIS patients were 0.665 and 0.691, respectively, according to the results of the ROC curve analysis; the corresponding specificities were 70.08% and 77.51%, and the corresponding sensitivities were 62.53% and 62.58%. The AUC for the combined prediction of ineffective treatment in AIS patients by serum Calectin-3 and sCD40L was 0.784, and the specificity and sensitivity were 65.18% and 81.25%, respectively. Serum Galectin-3 and sCD40L had respective AUCs of 0.774 and 0.838 for predicting a bad prognosis in AIS patients; their respective specificities were 67.58% and 75.36%, and their respective sensitivities were 75.06% and 80.04%. The combined prediction of serum Galectin-3 and sCD40L for the poor prognosis of AIS patients was not good. The AUC was 0.919, with a specificity and sensitivity of 60.05% and 90.63%, respectively. [Conclusion] Both the sCD40L level and the serum Galectin-3 level have some prognostic power for poor prognosis and ineffective treatment in AIS patients, and the combined detection of these two indicators can significantly improve the predictive efficacy.